Gold catalysed growth of silicon nanowires and core-shell heterostructures via solid-liquid-solid process and galvanic displacement - Ng, I.K.; Kok, K.Y.; Abidin, S.S.Z.; Saidin, N.U.; Choo, T.F.; Goh, B.T.; Chong, S.K.; Rahman, S.A. (2011)
Silicon nanowires (SiNWs) were first synthesised using Au coated p type Si (100) substrate via the solid-liquid-solid (SLS) process. The growth parameters were selectively varied to achieve various stages of growth for studying their effects on the morphology and microstructures of the nanowires (NWs). The SLS growth of SiNWs is discussed in the context of the experimental conditions used. Straight NWs of large aspect ratios, good crystallinity and morphology were generally obtained at a growth temperature of 1000 degrees C along with some worm-like amorphous structures. Te-Si NW core-shell structures were subsequently obtained via post-growth galvanic displacement of the SiNWs in an acidic HF electrolyte containing HTeO(2)(+) ions. The core-shell structures obtained were decorated with Te nanoparticles. This increases the NW surface areas and should have great potential in non-reflecting, photovoltaic and thermoelectric applications. Growth study on the SiNWs and Te-Si core-shell structures is presented using various microscopy, diffraction and probe based techniques for structural, morphological and chemical characterisations.